Neurofilament light protein levels in cerebrospinal fluid predict long‐term disability of Guillain‐Barré syndrome: A pilot study. (6th April 2018) - Axelsson, M.; Sjögren, M.; Andersen, O.; Blennow, K.; Zetterberg, H.; Lycke, J.
Abstract : Objectives: Although the recovery from Guillain‐Barré syndrome (GBS) is good in most patients, some develop permanent severe disability or even die. Early predictors would increase the likelihood to identify patients at risk for poor outcome at the acute stage, allowing them intensified therapeutic intervention. Materials and Method: Eighteen patients with a history of GBS 9‐17 years ago were reassessed with scoring of neurological disability and quality of life assessment (QoL). Their previous diagnostic work‐up included clinical examination with scoring of disability, neurophysiological investigation, a battery of serology tests for infections, and cerebrospinal fluid (CSF) examination. Aliquots of CSF were frozen, stored for 20‐28 years, and analyzed by ELISA for determination of neurofilament light protein (NFL) and glial fibrillary acidic protein (GFAP). Results: Patients with poor outcome (n = 3) had significantly higher NFL and GFAP levels at GBS nadir than those with good outcome (n = 15, P  <   .01 and P  <   .05, respectively). High NFL correlated with more prominent disability and worse QoL at long‐term follow‐up ( r  =   .694, P  <   .001, and SF 36 dimension physical component summary (PCS) ( r =−.65, P  <   .05), respectively, whereas GFAP did not correlate with clinical outcome or QoL. Conclusion: High NFL in CSF at the acute stage of GBS seems to predict long‐term outcome and might, together with neurophysiological and clinical measures, be useful in treatment decisions and clinical care of GBS.